2005
DOI: 10.5902/198050981721
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da inoculação com fungos ectomicorrízicos na produção de mudas de <i>Eucalyptus grandis</i> W. Hill ex Maiden em solo arenoso.

Abstract: RESUMOEste trabalho objetivou avaliar o efeito de diferentes inóculos e mistura de inóculos de fungos ectomicorrízicos sobre a produção de mudas de eucalipto em solo arenoso. O experimento foi desenvolvido em casa de vegetação. Os tratamentos foram quatro isolados e quatro mistura de inóculo de fungos ectomicorrízicos. Utilizou-se solo sob processo de arenização, coletado no município de São Francisco de Assis -RS. Avaliou-se a massa da parte aérea e radicular verde, massa da parte aérea seca, altura de planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
2
1
8
Order By: Relevance
“…Ectomycorrhizal fungi species differed in their capacity to increase leaf P concentration and content ( Figures 2a, 2b); however, they did not differ in terms of growth promotion (Figures 1a, 1b, 1c) and root colonization ability (Figure 1d), and they also raised leaf K and N concentration and content (Figures 2c, 2d, 2e, 2f). This similar behavior among EMF species observed in growth promotion, root colonization, and plant nutrition for some nutrients differs from most studies found in the literature (Alves et al, 2001;Silva et al, 2003;Souza et al, 2004Souza et al, , 2008Chen et al, 2006c).…”
Section: Inoculation Effectcontrasting
confidence: 51%
See 1 more Smart Citation
“…Ectomycorrhizal fungi species differed in their capacity to increase leaf P concentration and content ( Figures 2a, 2b); however, they did not differ in terms of growth promotion (Figures 1a, 1b, 1c) and root colonization ability (Figure 1d), and they also raised leaf K and N concentration and content (Figures 2c, 2d, 2e, 2f). This similar behavior among EMF species observed in growth promotion, root colonization, and plant nutrition for some nutrients differs from most studies found in the literature (Alves et al, 2001;Silva et al, 2003;Souza et al, 2004Souza et al, , 2008Chen et al, 2006c).…”
Section: Inoculation Effectcontrasting
confidence: 51%
“…In E. grandis seedlings inoculated with eight fungal treatments (four Pisolithus sp. isolates or mixtures thereof), increases in N content were observed for seven treatments and increases in K content for three, with the largest increases in N of 2.3 times and K of 1.9 times compared to the control (non-inoculated) (Silva et al, 2003). In E. urophylla seedlings inoculated with spores of six species or isolates of Scleroderma, increases of up to 2.2 times in N content and up to 1.7 times in K content was observed for seedling shoots (Chen et al, 2006b).…”
Section: Inoculation Effectmentioning
confidence: 99%
“…Os fungos ectomicorrízicos (fECM) são importantes agentes estruturadores de comunidades florestais, favorecendo a sucessão e resiliência, especialmente durante períodos de alterações climáticas (SMITH e READ, 2008). Estes micro-organismos interagem com espécies vegetais formando associação simbiótica mutualística, resultando em benefícios, como maior absorção de água e nutrientes e proteção das plantas a estresses bióticos e abióticos (KHAN, 2006;GRAZZIOTTI et al, 2001;FENG et al, 2002;SILVA et al, 2003a;PERA e PARLADÉ, 2005;ZEPPA et al, 2005;GÖHRE e PASZKOWSKI, 2006).…”
Section: Introductionunclassified
“…O bom desenvolvimento das mudas, uniformidade de produção e sanidade de um povoamento florestal, está diretamente ligado à qualidade das mudas que são levadas ao campo. Além disso, mudas com alto padrão de qualidade podem garantir melhores índices de sobrevivência, reduzindo, assim, a necessidade de gastos com replantio (SILVA et al, 2002). Além disso, Lopes (2005) ressaltou que, por se tratar de investimento no longo prazo, o rigor torna-se ainda maior, justificando a necessidade de produção de mudas de excelente qualidade.…”
Section: Introductionunclassified